How to Manage , Analyze, and Interpret Survey Data / Second Edition - Fink Arlene (Sage Publications, 2003)
An excellent introductory overview to selecting appropriate statistical tests - the purposes and prerequisites for using various statistical methods. How to Manage and Analyze and Interpret Survey Data: Learning Objectives, What Statistics Do for Surveys, Relationships and Comparisons, Selecting Commonly Used Statistical Methods for Surveys, Exercises, Suggested Readings, Glossary, About the Author.